2020
DOI: 10.3390/antibiotics9110835
|View full text |Cite
|
Sign up to set email alerts
|

Peri-Implant Diseases: Diagnosis, Clinical, Histological, Microbiological Characteristics and Treatment Strategies. A Narrative Review

Abstract: Since the use of dental implants is continuously increasing, it is imperative for dental practitioners to understand the nature and treatment of peri-implant diseases. The purpose of this manuscript is to comprehensively review peri-implant diseases, their characteristics, as well as their non-surgical and surgical treatment. To that end, the current literature was searched and a narrative review was conducted. It is essential that the case definitions described in the 2017 World Workshop on the Classification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 138 publications
0
37
1
Order By: Relevance
“…Peri-implantitis, with a prevalence ranging from 1.1% to 85% at the implant level and a higher early failure rate in maxillary implants than mandibular implants, occurs in the peri-implant region and often leads to inflammatory loss of supporting bone (188,271,272). Radiographic bone loss greater than or equal to 2 mm beyond the crestal bone level from the initial surgery, or greater than or equal to 3 mm apical to the most coronal part of the intraosseous portion of the implant is observed in periimplantitis, with even greater progression than that in periodontitis (273). Similar to periodontitis, peri-implantitis exhibits higher IL-1b levels in diseased tissues, and these changes may persist despite nonsurgical therapy (274)(275)(276).…”
Section: Inflammasomes In Peri-implantitismentioning
confidence: 99%
“…Peri-implantitis, with a prevalence ranging from 1.1% to 85% at the implant level and a higher early failure rate in maxillary implants than mandibular implants, occurs in the peri-implant region and often leads to inflammatory loss of supporting bone (188,271,272). Radiographic bone loss greater than or equal to 2 mm beyond the crestal bone level from the initial surgery, or greater than or equal to 3 mm apical to the most coronal part of the intraosseous portion of the implant is observed in periimplantitis, with even greater progression than that in periodontitis (273). Similar to periodontitis, peri-implantitis exhibits higher IL-1b levels in diseased tissues, and these changes may persist despite nonsurgical therapy (274)(275)(276).…”
Section: Inflammasomes In Peri-implantitismentioning
confidence: 99%
“…According to the scientific literature, dental implants show survival rates of up to 98% at 10 years [4][5][6]. However, the higher use of dental implants has been accompanied by an increase in the prevalence of peri-implant pathology [7]. A recent systematic review and meta-analysis reported an incidence of peri-implantitis ranging from 0.4% over 3 years, to 43.9% within 5 years after implant restoration [8].…”
Section: Introductionmentioning
confidence: 99%
“…Besides minor prosthetic complications (such as crown loosening or ceramic chipping), which are easy to solve, peri-implantitis is the most frequent complication and its resolution is a real challenge, the reason why so much has been published in recent years on this topic [9]. This pathology is defined clinically as the presence of signs of bleeding and/or suppuration in the peri-implant tissues on probing, increased probing depth and loss of 2 or more millimetres of marginal bone compared to previous radiographic recordings [7,10]. Its appearance is the result of a discrepancy between the bacterial challenge and the host response [11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations